Enhancement of rheological and mechanical properties of bitumen using styrene acrylonitrile copolymer. Issue 17 (21st January 2015) - Mousavi, Seyed Mojtaba; Farsi, Mohammad; Azizi, Mahdi
ABSTRACT: In this research, styrene acrylonitrile copolymer as a novel additive is used to modify rheological, mechanical and thermal properties of the base bitumen 70 penetration grade. Styrene acrylonitrile copolymer combines the rigidity of polystyrene with the hardness and thermal resistance of polyacrylonitrile to enhance viscoelastic property of the bitumen. To investigate the performance of the proposed mixture, shear complex module, phase angle, penetration, softening point, and reversibility of prepared samples are measured at different additive content and compared with the base bitumen. The results show that softening point of the base and modified samples are 49–86°C, respectively. The rheological properties of the base bitumen and modified samples are measured by a dynamic shear rheometer (DSR). The phase angle as elasticity measure decreases from 55° to 35° in the modified bitumen compared to the base bitumen. Generally, the experimental results showed that styrene acrylonitrile copolymer makes bitumen to be more stable at high temperatures and more flexible at low temperatures. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2015, 132, 41875. Abstract :